REDUPLIKASI SEMANTIK BAHASA INDONESIA: TELAAH NOVEL LASKAR PELANGI KARYA ANDREA HIRATA - Lala Zulfian Adha Sulfa; Amirudin Rahim; La Yani (PT. CASA CENDEKIA MEDIA, 2024)
This research aims to depict the forms and meanings of semantic reduplication in the Indonesian language within the novel